Analisis Qos (Quality Of Service) Dengan Metode Traffic Shaping Pada Jaringan Internet(Studi Kasus : Pt Toyonaga Indonesia) - Ahmad Turmudi; Fuad Abdul Majid (Teknik Informatika, Universitas Pelita Bangsa, 2019)
The development of communication services has developed very rapidly,One of them is the use of bandwidth to access the internet network, Therefore there must be a monitoring system that can know the quality of the network we are using The method used in this study is the literature method, namely the method of data collection carried out by collecting related data sources and experimental methods (observation) namely doing research on QOS (Quality Of Service) on the internet network at PT TOYONAGA INDONESIA which has been configured with RouterOS Router to do traffic shaping bandwidth The results of this study are that QOS (Quality of Service) quality at PT TOYONAGA INDONESIA is quite good by using the Traffic shaping Method but it does not demand the possibility that it can still change according to the conditions in the field, namely in terms of transmission distance and also the number of users, and in terms of things that affect network performance according to parameters (QOS), namely throughput, packet lost and delay. Keywords: Quality of service (Qos), Traffic Shaping Method, Pt Toyonaga Indonesia